Antimicrobial and Cytotoxic Potential of Eucalyptus Essential Oil-Based Nanoemulsions for Mouthwashes Application - Batista D.G. (2024)
© 2024 by the authors.Objective: An eucalyptus essential oil-based nanoemulsion was produced and evaluated for its antimicrobial properties against Streptococcus mutans and its cytotoxicity in the surface mucous cells of rabbits. Methods: The essential oil-based nanoemulsion was synthesized with two species of eucalyptus—Eucalyptus citriodora and Eucalyptus globulus—followed by physicochemical characterization and the determination of antimicrobial activity and cell viability. Subsequently, the mouthwash formulations (fluoride and fluoride-free) were functionalized with the nanoemulsion, and their in vitro antimicrobial actions were evaluated against S. mutans. Results: The nanoemulsion presented an average particle size of around 100 nm, a polydispersity index close to 0.3, a zeta potential between −19 and −30 mV, a pH close to 7, a spherical shape, and a cell viability above 50%. The antimicrobial activity analysis showed that the nanoemulsion was effective in the control of S. mutans. The mouthwashes functionalized with the nanoemulsion also presented bacteriostatic and bactericidal properties. Conclusions: The bio-based material produced with eucalyptus essential oil presented adequate physicochemical characteristics, with the potential to be used as an innovative material in preventive dentistry, contributing to the maintenance of oral and systemic health.